2017
DOI: 10.1016/j.jallcom.2017.05.103
|View full text |Cite
|
Sign up to set email alerts
|

On the eutectoid transformation behavior of the Ti-Zn system and its metastable phases

Abstract: To date, Zn has not been used as an alloying addition in structural Ti alloys. The main obstacle has been the disparity between their melting and vaporization temperatures. A novel processing technique was developed to create a Ti-Zn compound. The equilibrium phases and microstructures were studied by electron microscopy and x-ray diffraction techniques. Results show the presence of pearlitic domains of α-Ti (hexagonal closed packed crystal structure) and Ti2Zn (body center tetragonal structure) in regions tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…Moreover, this transformation contributes to the improvement of antibacterial property in biomedicine. Brice et al [40] found that β-Ti decomposes into α-Ti phase and Ti 2 Zn phase through active eutectoid transformation in waterquenched Zn-17 wt.% Ti alloy. The aggregation state of the decomposition products is flaky, and a good pearlite structure can be obtained under rapid cooling conditions.…”
Section: Microstructure Analysis Of Zr-17nb Alloy After Hcpeb Modificmentioning
confidence: 99%
“…Moreover, this transformation contributes to the improvement of antibacterial property in biomedicine. Brice et al [40] found that β-Ti decomposes into α-Ti phase and Ti 2 Zn phase through active eutectoid transformation in waterquenched Zn-17 wt.% Ti alloy. The aggregation state of the decomposition products is flaky, and a good pearlite structure can be obtained under rapid cooling conditions.…”
Section: Microstructure Analysis Of Zr-17nb Alloy After Hcpeb Modificmentioning
confidence: 99%
“…In Figure 6b, Zn-rich particles with a grain size below 100 nm are also found. It was reported that α-Ti had a slightly larger solubility of the Zn element at Ti-rich side of the Ti–Zn phase diagram [24]. Therefore, it can be speculated that the added Zn can react with Ti to form Zn-rich particles or dissolve into the α matrix to form a solid solution during FSP.…”
Section: Resultsmentioning
confidence: 99%
“…Zn is an important element in the human body, due to its role in the synthesis of a variety of enzymes, improving bone growth, and maintaining cell physiological function [22,23]. However, there are significant differences between the melting point of Ti (1660 °C) and the boiling point of Zn (907 °C), and, thus, it is difficult to add Zn into a Ti alloy via conventional metallurgical processing [24,25]. Brice et al [24] successfully prepared Ti–Zn compound via a self-designed reaction chamber, and found that α-Ti has a much larger solubility than in the equilibrium phase diagram.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brice et al (2017) citam que uso de Zn na metalurgia do Ti foi restrito a ambientes laboratoriais devido à disparidade entre o ponto de fusão do Ti (1660 ºC) e o ponto de fusão do Zn (420 ºC). Entretanto, para ligas ricas em Ti, altas taxa de resfriamento a partir de tratamento por bombardeio por feixe de elétrons e existência de formação martensítica perleitica competindo com formação eutetóide, estudos recentes sugerem formação de ligas Ti/Zn com porcentagem de zinco de 20%, pois a solubilidade do zinco em α-Ti é maior do que reportado porOkamoto (2008).3.5 Tratamento de fármacos por Processos Oxidativos Avançados (POA)Segundo Gros et al (2010), Uwai et al (2005) e Baranowska e Koper (2011), o propranolol (1-(isopropilamino)-3-(1-naftoxi)-2-propanol) apresenta peso molecular de 259,34 g/mol (Figura 2), é um beta-bloqueador largamente utilizado para o tratamento de angina, arritmia e hipertensão.…”
unclassified